Determining Conditions for Extraction of Phenolic Compounds From sage, Salvia officinalis using response serface technique (Latakia University Journal -Biological Sciences Series, 2021)
Samples of Salvia officinalis L. were collected in March 2020 from Albahlulia in Lattakia. The optimal conditions for the extraction of polyphenolic compounds (pc) from Salvia officinalis were determined using response surface methodology (RSM). A Central Composite Design was used to investigate the effects of three independent variables, namely solvent concentration, extraction temperature  and time on the response phenolic content. The independent variables were at three levels and their actual values selected on the basis of preliminary experimental results. A second-order polynomial model was used for predicting the response.Regression analysis showed that more than 95-97% of the variation was explained by the models. The optimal conditions for phenolic compounds extraction were found to be ethanol concentration of 51.5 v/v %, extraction temperature of 85.9 C°, extraction time of 74.4 min, for sage. Under  the optimum conditions the corresponding predicted response value for polyphenolic compounds was 2.83 mg EGA/g dry weight. The phenolics were extracted under optimum conditions to check the validity of model, and the experimental value was 2.91±0.02 mg galic acid equivalent /g dry weight from S.officinalis. The good agreement between predicted and ,experimental values indicated suitability of the model employed and the success of response surface methodology in optimizing the extraction conditions.